2013
DOI: 10.3354/dao02658
|View full text |Cite
|
Sign up to set email alerts
|

Baseline histopathological survey of a recently invading island population of ‘killer shrimp’, Dikerogammarus villosus

Abstract: Dikerogammarus villosus, an invasive amphipod, has recently been detected in UK freshwaters. To assess the potential for pathogen introduction with the invader, a year-long histopathology survey of the D. villosus population inhabiting the initial site of detection (Grafham Water, Cambridgeshire, UK) was conducted. Additional samples were collected from 2 other subsequently identified populations within the UK (Cardiff Bay and Norfolk Broads), and from established populations in France (River Rhine) and Poland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…This is particularly important, given fears that D. villosus will, in future, be carried across the Irish Sea to Ireland and the Isle of Man, and across the Atlantic to North America (Dick et al 2002;Casellato et al 2007). Recent histological analysis detected no evidence of infection with microsporidian parasites in two of the four known British populations of D. villosus (Cardiff Bay and Barton Broad) (Bojko et al 2013). A single microsporidian infection was discovered in a very large sample of D. villosus (N = 1,937) from a third British population (Grafham Water) but this parasite bore little resemblance to microsporidia known from the native range of D. villosus, suggesting that it may have been acquired locally (Bojko et al 2013).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…This is particularly important, given fears that D. villosus will, in future, be carried across the Irish Sea to Ireland and the Isle of Man, and across the Atlantic to North America (Dick et al 2002;Casellato et al 2007). Recent histological analysis detected no evidence of infection with microsporidian parasites in two of the four known British populations of D. villosus (Cardiff Bay and Barton Broad) (Bojko et al 2013). A single microsporidian infection was discovered in a very large sample of D. villosus (N = 1,937) from a third British population (Grafham Water) but this parasite bore little resemblance to microsporidia known from the native range of D. villosus, suggesting that it may have been acquired locally (Bojko et al 2013).…”
Section: Introductionmentioning
confidence: 96%
“…Recent histological analysis detected no evidence of infection with microsporidian parasites in two of the four known British populations of D. villosus (Cardiff Bay and Barton Broad) (Bojko et al 2013). A single microsporidian infection was discovered in a very large sample of D. villosus (N = 1,937) from a third British population (Grafham Water) but this parasite bore little resemblance to microsporidia known from the native range of D. villosus, suggesting that it may have been acquired locally (Bojko et al 2013). Microsporidian infections of amphipods can involve low numbers of parasites and such light infections may be overlooked during histological analysis.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Often, the pathogens of invasive hosts are little known or cryptic, requiring dedicated screening efforts to elucidate underlying parasites and pathogens that may be vectored to new habitats by non-native species (NNS) [2, 3]. …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, histopathology (Bojko et al, 2013) and PCRbased (Arundell et al, 2015) studies of UK populations of the invasive amphipod Dikerogammarus villosus showed a distinct lack of pathogens and parasites when compared in invasive range across central (Etxabe et al, 2015) populations of D. villosus is suggestive of single-point introductions, rather than continual incursion events as previously observed throughout its continental invasive (Bojko et al, 2013). In contrast, Dikerogammarus haemobaphes, presents UK populations with high prevalence of parasites, such as the Microsporidia Dictyocoela berillonum and Cucumispora ornate (Bojko et al, 2015) or the Nematoda Hysterothylacium deardorffoverstreetorum (Etxabe et al, 2015).…”
Section: Discussionmentioning
confidence: 99%